2013
DOI: 10.1021/pr400136p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Apolipoprotein-CIII Glycoforms with Ultrahigh Resolution MALDI-FTICR Mass Spectrometry of Human Sera

Abstract: Apolipoprotein-CIII (apoCIII) is an abundant blood glycoprotein associated with lipoprotein particles. Three different glycoforms have been described, all containing a mucin-type core-1 O-glycosylation with either zero, one or two sialic acids. Changes in the relative abundance of these glycoforms have been observed in a variety of different pathologies. In this study, ultrahigh resolution 15T MALDI Fourier transform ion cyclotron resonance (FTICR) MS was used to analyze apoCIII isoforms in serum protein profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…The evaluation of apoC-III isoforms is complicated by the fact that apoC-III 0 can be separated into a non-glycosylated form and glycosylated but non-sialylated forms (Bruneel et al 2008;Holleboom et al 2011;Nicolardi et al 2013a). Moreover, a recent MS study of 96 serum samples showed that 30 % of the individuals displayed an apoC-III pattern with additional glycosylated variants, characterised by fucosylation (Nicolardi et al 2013b). The relevance of these glycosylated non-sialylated variants of apoC-III, as of the C-terminal truncated forms, is yet unclear, but may explain somewhat contradictory results showing higher relative levels of non-and lesssialylated apoC-III in obese subjects than in lean subjects (Harvey et al 2009;Karlsson et al 2009), although obesity is generally associated with high triglyceride levels.…”
Section: Protein Isoforms Translational and Posttranslationalmentioning
confidence: 99%
“…The evaluation of apoC-III isoforms is complicated by the fact that apoC-III 0 can be separated into a non-glycosylated form and glycosylated but non-sialylated forms (Bruneel et al 2008;Holleboom et al 2011;Nicolardi et al 2013a). Moreover, a recent MS study of 96 serum samples showed that 30 % of the individuals displayed an apoC-III pattern with additional glycosylated variants, characterised by fucosylation (Nicolardi et al 2013b). The relevance of these glycosylated non-sialylated variants of apoC-III, as of the C-terminal truncated forms, is yet unclear, but may explain somewhat contradictory results showing higher relative levels of non-and lesssialylated apoC-III in obese subjects than in lean subjects (Harvey et al 2009;Karlsson et al 2009), although obesity is generally associated with high triglyceride levels.…”
Section: Protein Isoforms Translational and Posttranslationalmentioning
confidence: 99%
“…These steps include a baseline correction, smoothing, peak-picking, internal calibration or peak alignment, and transformation of the data in a format compatible with methods for statistical analysis. This data processing becomes more robust with improved quality of the profiles, and moreover, high quality data lead to improved statistical analysis [13]. In this context, resolving power, dynamic range, mass measurement accuracy, and precision of the mass analyser are parameters that define the quality of the signature.…”
Section: Resultsmentioning
confidence: 99%
“…Additional MS/MS-experiments can be performed on the FTICR itself (in electrospray mode), or using other MS-equipment. For example, we have recently reported on the identification of new apolipoprotein CIII glycoforms in MALDI-FTICR profiles that were recorded up to an m/z-value of 10,900 [13]. With the current extension of the m/z-range up to 15 kDa, these MALDI-FTICR profiles can be used for both bottomup and top-down identifications [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have focussed upon different glycosylation forms of specifi c proteins of interest. The application of high accurate mass MALDI profi ling after purifi cation allowed for the identifi cation of six new apolipoprotein CIII isoforms and their glycosylation status which may have a role in lipid metabolism and transport within the body and ApoCIII isoforms have been identifi ed as easy to purify by microscale tip preparation and able to allow for diagnoses in chronic hepatitis C and alcoholic liver cirrhosis [ 61 ]. A different approach sought to study the glycosylation status of membrane-type 1 matrix metalloproteinase (MT1-MMP) via MALDI mass spectrometric analysis after immunoprecipitation from cell lines as the glycosylation is required for cancer cell invasive processes [ 81 ].…”
Section: Post-translational Modifi Cation Analysismentioning
confidence: 99%